Pengaruh Alih Fungsi Telajakan Depan Rumah Menjadi Artshop terhadap Kenyamanan dan Estetika Lansekap Desa Tegallalang - HARIMBAWA, I WAYAN PASEK; SUKEWIJAYA, I MADE; UTAMI, NI WAYAN FEBRIANA (Jurnal Arsitektur Lansekap, 2015)
ABSTRACT The Effect of Telajakan -Front Yard Conversion into an Artshop Toward Human Comfort Index and Landscape Aesthetic in Tegallalang Village Telajakan , a Balinese typical home yard, has located in front, right or left, or in the back of the yard. The study only focused on telajakan front yard along the way of Tegallalang Village which is usually used as a garden or planted area, although many of them turning into an artshop. The purpose of the study was to determine the effect of telajakan conversion into an artshop using user’s comfort index and landscape aesthetic measurement. Methods used in this study was temperature humidity index (THI) with the data of temperature and humidity. In addition, to assessed the aesthetic quality of the landscape used scenic beauty estimation (SBE) method by taking a photo of each landscape element representing the land use. Result showed that user’s comport index was low (THI valued ranged from 24,47 to 27,39) and categorized as uncomfortable to the tropics area. Further, the aesthetic quality resulted that the lowest SBE quality was -80,21 and highest SBE quality was 138,42. The aesthetic quality of the majoring landscape along the way of Tegallalang valued as a low category (53,33%), medium category (28,88%), and high category (17,77%). As a results, the conversion of telajakan into an artshop caused low of user’s comfort index and low of aesthetic quality to the landscape.   Keywords : comfort index, landscape aesthetics, telajakan, temperature humidity index (THI), scenic beauty estimation (SBE).